Metabolic engineered E. coli for the production of (R)-1, 2-propanediol from biodiesel derived glycerol. Issue 8 (9th August 2022) - Sierra, Wilson; Menéndez, Pilar; Rodríguez Giordano, Sonia
Abstract: The development of the biodiesel industry with the concomitant production of glycerol as the major byproduct has had a negative impact on the glycerol market. The application of circular economy concepts has led to progress in production processes that use this residue as starting material. Propylene glycol has been identified as a potential destiny of glycerol surplus; however, the possibility of increasing this valorization from the existence of a stereogenic center has been scarcely explored. Using metabolic engineering in E. coli, a set of biocatalysts capable of biotransforming glycerol to ( R )-1, 2-propanediol has been designed, built, and evaluated. The simultaneous expression of a methylglyoxal reductase (Gre2p) and an aldehyde reductase (Ypr1p) both from S. cerevisiae origin, along with the overexpression of E. coli methylglyoxal synthase ( mgs A), resulted in an E. coli strain capable of producing enantiomerically pure (e.e.> 99%) ( R )-1, 2-propanediol from glycerol, in a concentration of 209 ± 9 mg.L -1 . The developed biocatalysts presented a satisfactory performance when crude glycerin obtained from biodiesel production process was used in place of glycerol.